Systematic Literature Review: Helping students learn mathematics through the Integrated Flipped Learning Model of Ethnomathematics and STEM (Architecture Image Studies, 2025)
Flipped learning is recognized for its flexibility and student-centered approach, integrating technology to enhance engagement and understanding. However, contradictions arise between the theoretical foundations of flipped learning and its practical implementation. Self-Determination Theory suggests that autonomy, competence, and relatedness should enhance motivation, yet many students experience anxiety and lack confidence when learning independently. Self-Regulated Learning Theory supports student autonomy, but real-world findings indicate that many learners struggle with self-discipline and require more structured guidance. Cognitive Load Theory emphasizes managing cognitive demands, yet the constructivist nature of flipped learning often increases cognitive overload rather than reducing it. Additionally, while Constructivism advocates deep, contextual learning, it sometimes conflicts with structured instructional approaches necessary for effective flipped learning. The integration of Ethnomathematics and STEM within the flipped classroom further exposes these contradictions. While ethnomathematics promotes cultural relevance in learning, it is often limited to artifact exploration rather than fostering deeper cognitive and moral engagement. Similarly, STEM integration aims to enhance interdisciplinary connections but faces challenges in meaningful application. To bridge these gaps, this study proposes the Social-Cognitive-Cultural Constructivist (CSCC) Learning Theory as a new framework for optimizing the flipped learning model. Further empirical studies are needed to refine this approach and ensure that flipped learning effectively aligns with its theoretical underpinnings while addressing practical challenges in student learning.